HOW DOES OMNI-CHANNEL EXPERIENCE SHAPES PURCHASE INTENTIONS OF LEGAL SERVICES: A STIMULUS-ORGANISM-RESPONSE PERSPECTIVE - YANG, Lisha; CAI, Yuanfeng (Asian Administration and Management Review, 2024)
Omni-channel retailing, an innovative strategy that integrates online and physical operations, is becoming increasingly popular among firms. This tendency emphasizes the necessity for a more profound understanding of consumers’ purchasing behavior within this context. The omni-channel research has been mainly concentrated on the retail and travel industries, with less attention paid to professional services. This research seeks to improve our understanding of how clients’ experiences across multiple channels influence their intention to purchase a certain professional service, particularly legal services, within a comprehensive omnichannel environment. Utilizing the Stimulus-Organism-Response theory, this study gathered 410 valid surveys by the offline snowball approach and subsequently employed PLS 4.0 to analyze the collected data. The results indicate that the five components of the omnichannel customer experience - connectivity, integration, consistency, flexibility, and personalization - have a significant influence on the perceived seamless, which in turn influences consumers’ intention to purchase legal services. The influence of personalization on the development of seamless experiences is particularly noteworthy among all these factors. The findings have theoretical implications and provide managerial recommendations for legal practitioners.